2022
DOI: 10.1186/s12879-022-07879-1
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 on the Belgian HIV epidemic: slowdown of HIV transmission and testing and adaptation of care

Abstract: Background To gain insight into the impact of the COVID-19 pandemic and containment measures on the HIV epidemic and services, this study aims to describe HIV trends in 2020 and compare them with previous years. Methods Belgian national HIV surveillance data 2017–2020 were analysed for trends in HIV testing, HIV diagnoses, VL measurements, ART uptake and PrEP purchase. Descriptive statistics from 2020 are compared to annual averages from 2017 to 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 25 publications
(24 reference statements)
1
3
0
Order By: Relevance
“…While our results rely on self-reported data, they are substantiated by laboratory data from Sweden, indicating a decrease in STI tests in 2020 versus 2019 of up to 25% varying by region [20]. Similar reductions occurred in HIV/STI tests in Belgium [21], France [22] and the wider european region [6].…”
Section: Discussionsupporting
confidence: 71%
“…While our results rely on self-reported data, they are substantiated by laboratory data from Sweden, indicating a decrease in STI tests in 2020 versus 2019 of up to 25% varying by region [20]. Similar reductions occurred in HIV/STI tests in Belgium [21], France [22] and the wider european region [6].…”
Section: Discussionsupporting
confidence: 71%
“…This decline could be attributed to the impact of the coronavirus (COVID-19) pandemic, which was first reported in Belgium on February 4, 2020. 28 In response to the pandemic, government health measures, such as lockdowns and transportation restrictions limited access to healthcare and services, affecting the detection of HIV cases, initiation of ART, and drug delivery. 28 Our study revealed that approximately one in three patients on ART were non-adherent over a 12-month follow-up period.…”
Section: Discussionmentioning
confidence: 99%
“…28 In response to the pandemic, government health measures, such as lockdowns and transportation restrictions limited access to healthcare and services, affecting the detection of HIV cases, initiation of ART, and drug delivery. 28 Our study revealed that approximately one in three patients on ART were non-adherent over a 12-month follow-up period. Another study that used the SMAQ and CASE questionnaire to assess adherence in 218 patients at the AIDS reference center of Ghent University Hospital in Belgium 13 found that 78.5% and 93.5% of patients adhered to ART using the SMAQ and CASE questionnaire, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation